Price-cost margin and bargaining power in the European Union - Ana Cristina Soares (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
Using firm-level data between 2004 and 2012 for eleven countries of the European Union (EU), we document the size of product and labour market imperfections within narrowly defined sectors including services which are virtually undocumented. Our findings suggest that perfect competition in both product and labour markets is widely rejected. Levels of the price-cost margin and union bargaining power tend to be higher in some service sectors depicting however substantial heterogeneity. Dispersion within sector and across countries tends to be higher in some services sectors assuming a less tradable nature which suggests that the Single Market integration is partial particularly relaxing the assumption of perfect competition in the labour market. We report also figures for the aggregate economy and show that Eastern countries tend to depict lower product and labour market imperfections compared to other countries in the EU. Also, we provide evidence in favour of a very limited adjustment of both product and labour market imperfections following the international and financial crisis.
Keywords: D40; J50; L10; 330; market imperfection; market structure; nash bargaining; European Union